Continuous hemofiltration improves the prognosis of bacterial sepsis complicated by liver dysfunction in children - Yun Cui; Xi Xiong; Fei Wang; Yuqian Ren; Chunxia Wang; Yucai Zhang (BMC, 2018)
Abstract Background Liver dysfunction is an independent risk factor for poor prognosis of patients with sepsis. The aim of this study is to evaluate the effects of continuous hemofiltration in patients with bacterial sepsis complicated by liver dysfunction. Methods We retrospectively analyzed the medical records of 27 cases of bacterial sepsis with liver dysfunction admitted to pediatric intensive care unit (PICU) of Shanghai Children's Hospital between January 2013 and December 2016. Results 28-day mortality and length of PICU stay were significantly reduced in the continuous hemofiltration group (n = 16) compared with the conventional management group (n = 11) (31.3% vs. 72.7%, 9 [4-23] vs. 14 [4-36], respectively, both P < 0.05). The interval time between PICU admission and continuous hemofiltration initiation was (22.06 ± 17.68) h, and the median time of continuous hemofiltration duration was 48 h (31-70 h). After 72 h hemofiltration, the levels of total bilirubin (TBIL), direct bilirubin (DBIL), total bile acids (TBA), ammonia, lactate (Lac), TNF-α and IL-6 were significantly decreased in the continuous hemofiltration group. Moreover, multivariate logistic regression analysis indicated that continuous hemofiltration treatment and the TBIL level were independently associated with 28-day mortality of patients with bacterial sepsis complicated by liver dysfunction. Conclusions Continuous hemofiltration significantly decreases the serum levels of TBIL, DBIL, TBA, Lac, ammonia, TNF-α, IL-6, and improves 28-day mortality of patients with bacterial sepsis complicated by liver dysfunction.